PROFESSIONAL AND PEDAGOGICAL ACTIVITY OF HIGHER MEDICAL EDUCATION INSTITUTIONS’ LECTURERS IN THE CONTEXT OF SYSTEMATIC APPROACH - Belyaeva, E.N. (World of Medicine and Biology, 2014)
The article foregrounds the content of concepts «pedagogical activity» and «professional pedagogical activity». In the context of systematic approach, the analysis of professional pedagogical activity of lecturers at higher medical education institutions has been performed. It is displayed that this activity is inherently integrative, combining the following components: objective, scientific, psychological, pedagogical, ideological and therapeutic (for lecturers at clinical departments). The functional components of educational system, such as motivational, adaptive, stimulating, cybernetic, technologic, diagnostic, monitoring, communication and projecting have been presented.